Effect Of Heat Treatment And Equal Channel Angular Pressing On The Microstructures, Hardness And Wear Resistance Of A356 Aluminium Alloy With Tib2 - Syukron, Muhammad (2016)
Equal Channel Angular Pressing (ECAP) is a relatively simple procedure to produce ultra-fine grains and there is a potential for use in commercial metal processing. However processing difficulties may arise during ECAP because of the occurrence of cracking. In the present work, A356 aluminium alloy and A356 aluminium alloy with varying addition of TiB2 grain refiner (0.75, 1.5, 2.63 wt.%) were prepared via gravity die casting. The as-cast A356 aluminium alloy specimens with TiB2 addition contains hard phase of eutectic Si, hard particles of TiB2 and TiAl3 which potentially cause cracking during ECAP processing therefore heat treatments were carried out prior to ECAP. The heat treatments were annealing at 540°C for 8 hours followed by furnace cooling, solution treatment at 540°C for 4 hours followed by water quenching, and aging treatment at 110°C, 155°C, 200°C, 245°C and 290°C for 3 hours. The heat treated specimens were processed through 4- pass ECAP via BA route (rotation 90°). The combinations between heat treatment and (ECAP) were done to analyze the effect of both processes on microstructures, hardness and wear resistance of the specimens. The specimens were characterized with optical microscope, SEM, EBSD, TEM, hardness and wear test. The 4-pass ECAP processing increased significantly the hardness of the specimens which have relatively soft matrix. The relatively soft matrix in combination with TiB2 and Si particles gave benefit in accelerating multiplication of dislocation density leading to grain refinement during ECAP processing. From the overall considerations of hardness, average grain size and wear rate, pre-ECAP solution treatment specimen has the best value in general, then followed by post-ECAP aging 155°C specimen in the second rank.